Quality assessment of structural steel in mining equipment manufacture - Korotkov Aleksandr; Korotkova Lidia (MATEC Web of Conferences, 2017)
The relevance of this work is to form a methodical, scientific-based approach and the application of this experience in solving problems of quality control and improvement, as well as to identify ways of eliminating defects and small lifetime of the materials, used in critical parts and units of mining equipment. The aim of scientific research of the article is the study of discrepancy of structural steels quality problem, used for the manufacture of parts and components of mining equipment, established by standards. The goals are also, development and practical application of quality control methods in delivery condition and at all main stages of parts manufacture in accordance with the current state standards. As a result of steel quality complex control in delivery condition, it was possible to identify: the deviation of the chemical composition of steels and alloys, macrodefects, microdefects, deviation in hardness. Practical recommendations to eliminate and reduce and prevent the defects in parts and units used in mining engineering were developed. The paper presents practical experience in evaluation the quality of construction materials, which may be useful in design, manufacture and operation of mining industry and related manufacture industries.